Shikhara (superstructure) above the main Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
Seen here is the front side, east-facing, of the shikhara (superstructure) above the main Suswani Mata Temple which is of a Latina Nagara (mon-spired) variety. Square on plan, the shikhara is composed of curvilinear bands. A vertical band of aedicules arranged in a descending manner from top to bottom on the corners. The central band is plain.